Leukocytes telomere length as a biomarker of adverse drug reactions induced by Osimertinib in advanced non-small cell lung cancer - Narumol Trachu; Thanyanan Reungwetwattana; Jennis Meanwatthana; Chonlaphat Sukasem; Teerapat Majam; Wacharapol Saengsiwaritt; Jiraphun Jittikoon; Wanvisa Udomsinprasert (Scientific Reports)
Abstract This study aimed to measure relative telomere length (RTL) in blood leukocytes of advanced-stage NSCLC patients either with or without Osimertinib-induced ADRs and determine whether RTL could serve as a biomarker of Osimertinib-induced ADRs. Blood leukocytes RTL were measured in 63 advanced-stage NSCLC patients and 62 age-matched healthy controls using real-time polymerase chain reaction. In patients with advanced-stage NSCLC, RTL was significantly shorter than that in healthy controls (P < 0.001). Compared to patients without ADRs and those with mild/moderate ADRs, patients with severe ADRs exhibited significantly decreased RTL (P < 0.001, P < 0.001, respectively). ROC curve analysis uncovered a diagnostic value of RTL as a biomarker of Osimertinib-induced ADRs (AUC = 1.000, P < 0.001). Kaplan-Meier analysis revealed a significant association between shorter RTL and increased cumulative incidence of Osimertinib-induced ADRs in patients with advanced-stage NSCLC (P < 0.001). Shorter RTL in blood leukocytes would reflect the occurrence of Osimertinib-induced ADRs and might emerge as a promising biomarker for identifying advanced-stage NSCLC patients who are at risk of experiencing Osimertinib-induced ADRs, particularly those with severe ADRs.